The Migration Turn and Eastern Europe A Global Historical Sociological Analysis - Melegh, Attila (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Using Marxist and Polanyian frameworks, this book examines the structural and discursive transformation that can explain the polarization of migration debates and within the rise of nationalist anti-migrant discourses in Europe with a special attention to Eastern Europe and Hungary. It goes beyond the mainstream explanations of these phenomena that uses nationalist propaganda as causal factors and instead argues that the rise of anti-immigration currents cannot be understood without a dialectical and historical analysis of the material and discursive transformations, most importantly marketization and related reification. Drawing from thinkers such as Lukács, Polanyi, and Gramsci as well as diverse empirical sources including demographic studies, historical modelling, and discourse analyses, Migration Turn and Eastern Europe is a unique and rigorous study of one of the most pressing and puzzling political and sociological questions of ourtime. Attila Melegh is Associate Professor at the Institute of Communication and Sociology, Corvinus University of Budapest, UK, and Senior Researcher at the Demographic Research Institute, Budapest, Hungary.
1. Introduction: Trillion Dollar Bill or a Nightmare? -- 2. The Migration Turn and the Demographic Discourses in the 1980s -- 3. Historical Material Structures and Processes- 4. Discursive Changes -- 5. Conclusion.
Keywords: Political science; Europe -- Politics and government; Political sociology; Political science -- Philosophy; Political Theory; European Politics; Political Sociology; Political Philosophy